2015
DOI: 10.1111/jace.13643
|View full text |Cite
|
Sign up to set email alerts
|

Low‐Temperature Control of Twins and Abnormal Grain Growth in BaTiO3

Abstract: The microstructure of polycrystalline barium titanate (BaTiO3) thin films processed with a liquid‐phase can be controlled by the crystallographic orientation of the underlying sapphire substrate. During postdeposition crystallization, the tendency for {111} twin nucleation, which drives subsequent abnormal grain growth, depends upon the specific sapphire facet. Specifically, tilting away from the close‐packed c‐plane modifies the orientation, morphology, and relative amount of an interfacial BaAl2O4 second pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…shows permittivity measurements from room temperature to 200°C from several different reports. The systems shown were selected on the basis of high material density and overall quality and to illustrate the differences between a 75‐nm‐thick strain‐free single crystal, a 70 nm grain size bulk ceramic, a 55 nm grain size film (~180 nm thick) on platinized silicon, a 130 nm grain size film (~500 nm thick) on rigid a ‐sapphire (with top interdigitated contacts), and a 157 nm grain size film (~650 nm thick) on flexible copper foil . The latter two example thin films were processed with added BaO–B 2 O 3 (869°C eutectic composition) to enhance densification and grain growth at lower temperatures.…”
Section: Electrical and Mechanical Boundary Conditionsmentioning
confidence: 99%
See 3 more Smart Citations
“…shows permittivity measurements from room temperature to 200°C from several different reports. The systems shown were selected on the basis of high material density and overall quality and to illustrate the differences between a 75‐nm‐thick strain‐free single crystal, a 70 nm grain size bulk ceramic, a 55 nm grain size film (~180 nm thick) on platinized silicon, a 130 nm grain size film (~500 nm thick) on rigid a ‐sapphire (with top interdigitated contacts), and a 157 nm grain size film (~650 nm thick) on flexible copper foil . The latter two example thin films were processed with added BaO–B 2 O 3 (869°C eutectic composition) to enhance densification and grain growth at lower temperatures.…”
Section: Electrical and Mechanical Boundary Conditionsmentioning
confidence: 99%
“…In this particular comparison, grain sizes are similar, processing temperatures are identical (900°C), and the liquid forming sintering aide is added to each. However, for films on sapphire the final dielectric constant is roughly 67% lower than for films on flexible substrates . Ferroelectric films on flexible substrates are one of few examples where bulk‐like permittivities, dielectric tuning, and piezoelectric coefficients are present at room temperature.…”
Section: Electrical and Mechanical Boundary Conditionsmentioning
confidence: 99%
See 2 more Smart Citations
“…This may be particularly relevant for the production of BTO-based electroceramics, which involves sintering as the key process step after shaping the workable mass (powder or an aqueous paste). Our literature research revealed that there exist several reports about abnormal grain growth of BTO nanomaterials after processing and sintering at temperatures T > 1100 °C. One study even described abnormal grain growth even within electrospun fibers, where water was also inevitably involved in the preceding materials processing. The authors clearly indicate that an intermediate BaCO 3 phase has formed, which is also consistent with independent report, but decomposes at temperatures above 700 °C.…”
Section: Results and Discussionmentioning
confidence: 97%